(untitled) (USA, 2000)
Biochemistry & Molecular Biology of Plants is a major contribution to the plant sciences literature, superbly edited by three distinguished scientists, Bob B. Buchanan, Wilhelm Gruissem, and Russell L. Jones, with contributions from more than 50 world-renowned scientists. With over 1,400 pages, 1,100 full-colour original drawings and 500 photographs this work qualifies, in the words of the Science reviewer
Thâm cứu sinh lý thực vật
Keywords: Botanical chemistry,Plant molecular biology,Hóa học thực vật,Sinh học phân tử cây